BIOCOMPABILITY TEST OF HARUAN FISH (Channa striata) BONE HYDROXYAPATITE TO FIBROBLAST CELL AS PERIODONTAL POCKET THERAPY (In Vitro Study on BHK-21 Fibroblast Cell with Hydroxyapatite of Haruan Fish Bone (Channa striata) as Bone Graft Material) - Maulidah Maulidah; Irnamanda DH; Fransiska Uli Arta Panjaitan (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Periodontitis is an inflammation of the soft tissues and hard tissues that support the tooth characterized by periodontal pocket formation, recession to resorption of alveolar bone. So far, alveolar bone resorption caused by periodontitis can be treated with bone graft therapy. Xenograft is a type of bone graft that has many advantages such as can be obtained from natural materials, low in price and has minimal virus transmission. Hydroxyapatite of haruan fish bone is a type of xenograft material that has never been applied in medical field. Objective: This study aims to analyze the biocompatibility of haruan fish bone hydroxyapatite (Channa striata) against BHK-21 fibroblast cells via viability. Method: This was a laboratory experimental study with posttest only control group design, using MTT assay method and BHK-21 fibroblast cell viability was calculated using optical density formula. Results: The concentrations of 0,2109 mg/ml, 0,4218 mg/ml 0,8437 mg/ml, 1,6875 mg/ml, 3,3375 mg/ml and 6,75 mg/ml were biocompatible against fibroblast cells BHK-21 whereas at concentrations of 54 mg/ml, 27 mg/ml and 13,5 mg/ml were toxic to BHK-21 fibroblast cells. One Way Anova test and Bonferroni test showed concentrations of 54 mg/ml, 27 mg/ml and 13,5 mg/ml had significant differences to other concentrations. Conclusion: Hydroxyapatite of haruan fish bone (Channa striata) at some concentration is biocompatible against BHK-21 fibroblast cells.